1980
DOI: 10.1295/polymj.12.899
|View full text |Cite
|
Sign up to set email alerts
|

Polymerizability of 1,3-Disubstituted 1,3-Butadiene and Preparation of New Alternating Copolymer

Abstract: The polymerizabilities of ethyl trans-4-ethoxy-2,4-pentadienoate (EEP) and trans-4-ethoxy-2,4-pentadienonitrile (EPN) initiated by radical or ionic species were investigated. High-molecular-weight polymers were-obtained from both monomers only by radical polymerization. Spectroscopic study showed the polymers to be composed of the 2,5-addition units of the corresponding monomers. The hydrogenation of these polymers gave alternating copolymers of ethyl vinyl ether with ethyl acrylate and of ketene with acryloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…However, several 1,3‐substituted butadienes have been synthesized, including ethylene/vinyl alcohol, [ 82 ] styrene/ethylene, [ 77 ] and vinyl ether/acrylate. [ 83 ]…”
Section: Selection Of Monomersmentioning
confidence: 99%
“…However, several 1,3‐substituted butadienes have been synthesized, including ethylene/vinyl alcohol, [ 82 ] styrene/ethylene, [ 77 ] and vinyl ether/acrylate. [ 83 ]…”
Section: Selection Of Monomersmentioning
confidence: 99%
“…Each peak of poly-(EEP) was resonably assigned by the 1 ,4-addition unit as previously reported. 15 In poly(EP) (Figure 4), no signal could be detected in the region from 4.5 ppm to 5.2 ppm where vinilidene protons of the vinyl group binding to a carbon atom gave a resonance peak. 20 Therefore, the possibility of a 1,2-addition is ruled out.…”
Section: Esr Spectra Of Propagating Radicalsmentioning
confidence: 99%
“…EXPERIMENTAL Ethyl 4-ethoxy-2,4-pentadienoate (EEP, trans: cis= 92 : 8) was prepared as shown in a previous paper. 15 Bp 60°C/0.5 mm. Ethyl trans-4-methyl-2,4-pentadienoate (EMP) and ethyl 2,4-pentadienonate (EP) were similarly prepared from methacrolein and acrolein, respectively.…”
mentioning
confidence: 99%
“…reported the radical polymerizations of ethyl trans ‐4‐ethoxy‐2,4‐pentadienoate and trans ‐4‐ethoxyl‐2,4‐pentadienonitrile. The resulting polymers were hydrogenated to give alternating copolymers of ethyl vinyl ether/ethyl acrylate and of ketene/acrylonitrile, respectively . Li et al .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting polymers were hydrogenated to give alternating copolymers of ethyl vinyl ether/ethyl acrylate and of ketene/ acrylonitrile, respectively. 23 Li et al reported anionic polymerization of 1-phenyl-3-isopropyl-1,3-butadiene (PhiPrBu). The polymerization was highly regioselective and the resulting product was dehydrogenated into substituted polyacetylene with alternating sequence of the substituents.…”
mentioning
confidence: 99%